2023
DOI: 10.3171/2023.8.focus23466
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review on the state of racial disparities literature in the treatment of neurosurgical disease: a call for action

Edwin Owolo,
Andreas Seas,
Brandon Bishop
et al.

Abstract: OBJECTIVE Racial disparities are ubiquitous across medicine in the US. This study aims to assess the evidence of racial disparities within neurosurgery and across its subspecialties, with a specific goal of quantifying the distribution of articles devoted to either identifying, understanding, or reducing disparities. METHODS The authors searched the MEDLINE, EMBASE, and Scopus databases by using keywords to represent the concepts of neurosurgery, patients, racial disparities, and specific study types. Two in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Nonetheless, the vast majority of research on disparities within neurosurgery is still focused on the identification of disparities associated with treatment of neurosurgical diseases. A 2023 review investigating the current state of racial disparities literature within neurosurgical patients found that only 15.1% and 1.3% of the literature were devoted to understanding the root causes and proposing solutions, respectively, highlighting the importance of continued research [54]. We therefore propose provider, patient, community, and policy and organizational interventions aimed at addressing disparities in access to DBS as a treatment for advanced PD.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, the vast majority of research on disparities within neurosurgery is still focused on the identification of disparities associated with treatment of neurosurgical diseases. A 2023 review investigating the current state of racial disparities literature within neurosurgical patients found that only 15.1% and 1.3% of the literature were devoted to understanding the root causes and proposing solutions, respectively, highlighting the importance of continued research [54]. We therefore propose provider, patient, community, and policy and organizational interventions aimed at addressing disparities in access to DBS as a treatment for advanced PD.…”
Section: Resultsmentioning
confidence: 99%